Tissue‐Engineered Vascular Grafts: Effects of Braiding Parameters on Tissue Engineered Vascular Graft Development (Adv. Healthcare Mater. 24/2020). Issue 24 (16th December 2020) - Zbinden, Jacob C.; Blum, Kevin M.; Berman, Alycia G.; Ramachandra, Abhay B.; Szafron, Jason M.; Kerr, Katherine E.; Anderson, Jennifer L.; Sangha, Gurneet S.; Earl, Conner C.; Nigh, Noah R.; Mirhaidari, Gabriel J. M.; Reinhardt, James W.; et al.
Abstract : In article number 2001093 by Jacob C. Zbinden, Christopher K. Breuer, and co‐workers, tissue engineered arterial grafts are created from braided poly(glycolic acid) fibers at the boundaries of the manufacturable design space with and without a poly(glycerol sebacate) coating and evaluated in a mouse intrarenal aortic model. Implants are followed with 4D ultrasound and explants are evaluated with biaxial mechanical testing and histological analysis.